Total synthesis and biological evaluation of nannocystin analogues modified at the polyketide phenyl moiety. Issue 33 (15th August 2018) - Tian, Yunfeng; Ding, Yahui; Xu, Xiaolong; Bai, Yanju; Tang, Yang; Hao, Xin; Zhang, Weicheng; Chen, Yue
Graphical abstract: Highlights: 10 nannocystin analogues varying at the polyketide phenyl moiety were synthesized. These compounds were tested against both cancer cell lines and normal cell lines. All potent compounds inhibited the growth of both cancerous and normal cell lines. Abstract: Total synthesis of a focused set of 10 nannocystin analogues3a –3j modified at the polyketide phenyl moiety was reported. These compounds were evaluated against three cancer cell lines. Compared with the naturally occurring congener3a, the other synthetic variants either preserved or lose antiproliferative activity at varying degrees. Moreover, the potent analogues also displayed comparable levels of cytotoxicity toward two normal cell lines.